Analisis Yuridis Kewenangan Fungsi DPRD Kota Sukabumi berdasarkan Peraturan Pemerintah Nomor 12 Tahun 2018 - Ita Mulyawati Dewi; Agus Rasyid Chandra Wijaya (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the authority of the Regional People's Representative Council (DPRD) of Sukabumi City based on Government Regulation Number 12 of 2018 concerning Guidelines for the Preparation of Standing Orders of Regional People's Representative Councils of Provinces, Regencies, and Cities. The authority of the DPRD is a crucial element in ensuring the effective implementation of regional governance under the principle of check and balances. This research employs a normative juridical legal research method with a descriptive-analytical specification. The approaches used include the statute approach, conceptual approach, and case approach. The analysis is conducted using the Authority Theory of Philipus M. Hadjon, which classifies sources of authority into attribution, delegation, and mandate. The results indicate that the authority of the DPRD of Sukabumi City in exercising its supervisory function originates from constitutional attribution directly conferred by Article 20A paragraph (1) of the 1945 Constitution, reinforced by Law Number 17 of 2014, Law Number 23 of 2014, and operationalized through Government Regulation Number 12 of 2018 Articles 19, 21, and 22. Such authority is imperative in nature, not merely discretionary. Failure to exercise it constitutes a violation of the constitutional mandate, resulting in what Hadjon refers to as a legal oversight vacuum that enables systematic and recurring legal violations.